1994
DOI: 10.1038/ng0694-189
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the xeroderma pigmentosum group D DNA repair/transcription gene in patients with trichothiodystrophy

Abstract: DNA repair defects in the xeroderma pigmentosum (XP) group D complementation group can be associated with the clinical features of two quite different disorders; XP, a sun-sensitive and cancer-prone disorder, or trichothiodystrophy (TTD) which is characterized by sulphur-deficient brittle hair and a variety of other associated abnormalities, but no skin cancer. The XPD gene product, a DNA helicase, is required for nucleotide excision repair and recent evidence has demonstrated a role in transcription. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 31 publications
2
63
0
2
Order By: Relevance
“…Homologous genes designated XPB, XPD, p62, and p44, respectively, encode subunits of TFIIH(BTF2) in human cells (4,7,13,19,20). Mutations in the XPB and XPD genes are associated with several human hereditary diseases, including xeroderma pigmentosum, xeroderma pigmentosum with Cockayne's syndrome, and trichothiodystrophy (1,27).…”
mentioning
confidence: 99%
“…Homologous genes designated XPB, XPD, p62, and p44, respectively, encode subunits of TFIIH(BTF2) in human cells (4,7,13,19,20). Mutations in the XPB and XPD genes are associated with several human hereditary diseases, including xeroderma pigmentosum, xeroderma pigmentosum with Cockayne's syndrome, and trichothiodystrophy (1,27).…”
mentioning
confidence: 99%
“…It has been proposed that subtle alterations in transcription, caused by mutations in TFIIH subunits, can result in deficiencies in certain proteins whose expression is critically dependent on the level of transcription (35,37). Furthermore it has been suggested that the features of XP largely result from defective DNA repair, whereas many of the features of TTD may be a consequence of transcriptional alterations (14,35,37). The finding that the causative mutations in the XPD gene are located at different sites within the gene in XP-D and TTD patients (refs.…”
Section: Discussionmentioning
confidence: 99%
“…The first was the cloning of the ERCC2 gene by Christine Webber and Larry Thompson and demonstration that this was the XPD gene [61], the second was the seminal discovery by the group of Jean-Marc Egly in collaboration with the Rotterdam group that XPB and XPD were components of the transcription factor TFIIH, which had two functions, in NER and transcription [62]. Following on from these exciting findings we were able to identify the first mutations in the XPD gene, in TTD patients [63], and subsequently in many others and, importantly, we were able to show that each mutation site is disease-specific. R683W, found in the majority of XP patients in the XP-D group, has never been found in a TTD patient, whereas, R112H and R722W, fairly common in TTD, are never found in XP patients [64].…”
Section: Xp Variants Cockayne Syndrome and Other Repair-deficient DImentioning
confidence: 95%